2018
DOI: 10.1016/j.ebiom.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The enhancer RNA lnc-SLC4A1-1 epigenetically regulates unexplained recurrent pregnancy loss (URPL) by activating CXCL8 and NF-kB pathway

Abstract: BackgroundEnhancer RNAs (eRNAs) are a group of lncRNAs transcribed from enhancers, whose regulatory effects on gene expression are an emerging area of interest. However, the role of eRNAs in regulating trophoblast cells and unexplained recurrent pregnancy loss (URPL) remains elusive.MethodsWe profiled eRNAs in villi from URPL patients and matched controls by RNA-seq. Functions of URPL-related eRNAs were further investigated in vitro.ResultsWe identified lnc-SLC4A1-1, which was transcribed from an active enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 53 publications
1
74
0
Order By: Relevance
“…In addition to promoter-enhancer looping and histone modifications, eRNAs interact with transcriptional machinery such as transcription factors, BRD4, and RNAP II. eRNA knockdown decreases binding of transcription factors at respective promoter and enhancer loci, perhaps due to loss of the "transcription factor trapping" mechanism previously discussed (Sigova et al, 2015;Spurlock et al, 2017;Huang Z. et al, 2018). Additionally, the bromodomains of BRD4 have been shown to directly interact with eRNA.…”
Section: Regulation Of Transcriptional Machinerymentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to promoter-enhancer looping and histone modifications, eRNAs interact with transcriptional machinery such as transcription factors, BRD4, and RNAP II. eRNA knockdown decreases binding of transcription factors at respective promoter and enhancer loci, perhaps due to loss of the "transcription factor trapping" mechanism previously discussed (Sigova et al, 2015;Spurlock et al, 2017;Huang Z. et al, 2018). Additionally, the bromodomains of BRD4 have been shown to directly interact with eRNA.…”
Section: Regulation Of Transcriptional Machinerymentioning
confidence: 98%
“…RNAs tethered near enhancer loci were shown to increase the presence of YY1 specifically at those loci, perhaps due to "transcription factor trapping" wherein nascent RNA from enhancers and promoters increase the affinity of otherwise weak DNA-TF interactions creating a kinetic sink that would "trap" escaped transcription factors (Sigova et al, 2015). Such a model may explain observations that eRNA increases the binding of transcription factors such as c-Jun and NF-κB to target loci (Shii et al, 2017;Spurlock et al, 2017;Huang Z. et al, 2018). An emerging idea for how eRNAs may interact with large numbers of proteins is through phase separation.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, URM is currently considered to be mainly associated with immune factors . Studies have shown that abnormal expression of chemokines may be associated with miscarriage . A series of studies have shown that the abnormal expression of chemokines and their receptors at the maternal‐fetal interface may be associated with URM, such as CCL2, CXCL12, and CXCL13 .…”
Section: The Role Of Cxcl16 In Pathological Pregnancymentioning
confidence: 99%
“…1,95 Studies have shown that abnormal expression of chemokines may be associated with miscarriage. 27,96,97 A series of studies have shown that the abnormal expression of chemokines and their receptors at the maternal-fetal interface may be associated with URM, such as CCL2, CXCL12, and CXCL13. 27,96,98,99 Other studies have also reported, through immunohistochemistry and immunoblotting, that CXCL16 expression of the villus was decreased in patients who had undergone spontaneous miscarriage compared with normal pregnant women.…”
Section: Recurrent Miscarriagementioning
confidence: 99%